Experimental examination of large capacity liFePO4 battery pack at high temperature and rapid discharge using novel liquid cooling strategy. (17th October 2017) - Wang, Cong; Zhang, Guoqing; Li, Xinxi; Huang, Jin; Wang, Ziyuan; Lv, Youfu; Meng, Like; Situ, Wenfu; Rao, Mumin
Summary: To overcome the significant amounts of heat generated by large‐capacity battery modules under high‐temperature and rapid‐discharge conditions, a new liquid cooling strategy based on thermal silica plates was designed and developed. The superior thermal conductivity of the thermal silica plate combined with the excellent cooling effect of water led to a feasible and effective composite liquid cooling system during long cycle testing. The experimental results showed that the addition of thermal silica plates can greatly improve the cooling capacity that can allow the maximum temperature difference to be controlled at 6.1°C and reduce the maximum temperature of the battery module by 11.3°C, but still outside the optimum operating temperature range. The water flow significantly enhanced the cooling performance/stability, and slight temperature fluctuations were observed during cycling. The cooling performance obviously improved as the flow rate rose. When the velocity reached a critical value, further increase in water flow rate induced a slight influence on the cooling capacity due to the limitation of the materials. The maximum temperature ( T max ) could be reduced to 48.7°C, and temperature difference (∆T) could be maintained within 5°C when the water flow velocity increased to 4 mL/s, which was determined as the best value. The energy consumed by the water pump is only 1.37% of the total energy of the battery module. Overall, these findings should provide novel strategies for the design and optimization of battery thermal management system. Abstract : A thermal silica plate/liquid coupled cooled plate (SLCP) was designed for large‐capacity battery module to manage large amounts of heat generated under high temperature and rapid discharge. The superior thermal conductivity of the thermal silica plate combined with the excellent cooling effect of water led to a feasible and effective composite liquid cooling system during long cycle testing. The battery module with SLCP can effectively balance the maximum temperature difference of the module and improve the temperature uniformity of modules.